Evaluation of the Effects of ss-Adrenergic Receptor-Propranolol on Osseointegration of the Titanium Implants - Talo Yildirim, Tuba; Dundar, Serkan; Bozoglan, Alihan; Karaman, Tahir; Tekin, Samet; Kahraman, Onur Evren (Lippincott Williams & Wilkins, 2021)
This study aimed to investigate the effects of systemic propranol on the osseointegration of titanium implants. After the surgical insertion of titanium implants into the metaphyseal part of the tibial bone, the rats were randomly divided into 2 equal groups: the control (CNT) (n = 10) and propranol group (P) (n = 10); CNT: Rats received no further treatment during the 4 week experimental period after surgery. Rats received 10 mg/kg propranol in every day during the 4 week experimental period in PRP group after the surgical insertion of the implants. After the experimental period, the rats were euthanized, blood serum were collected to biochemical analysis and the implants and surrounding bone tissues were used for the histopathologic analysis. To analysis of the data between tests and controls student T test was used. There were no significant differences in the biochemical parameters (alcaline phosphatase, calcium, phosphor) of the groups (P > 0.05). Bone implant connection (BIC) ratios was detected higher in test animals compared with the controls (P < 0.05). Systemic propranolol may increases titanium implant osseointegration.
Keywords: Beta adrenergic receptor; osseointegration; propranol; titanium implant